Navigating the Pandemic: Social-Legal Approaches for Establishing a Specialized Infectious Disease Hospital - Situmeang, Ampuan; Shahrullah, Rina Shahriyani; Aprisanti, Aprisanti; Ong’eta, Wyclife (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
In accordance with Government Regulation